Why Do Programmers Earn More in Houston than Hyderabad? Evidence from Randomized Processing of US Visas. - Clemens, Michael A (American Economic Review, 2013)
Why do workers earn so much more in the United States than in India? This study compares the earnings of workers in the two countries in a unique setting. The product is perfectly tradable (software), technology differences are nil (they are members of the same work team), and the workers are identical in expectation (those who enter the United States are chosen by natural randomization). The results suggest that output tradability, technology, and human capital together explain much less than half of the earnings gap. Location itself may have large effects on individual workers' wages and productivity, for reasons poorly understood.